Mamfaatkan Limbah Plastik Jenis Styrofoam Untuk Pembuatan Paving Block - Harahap, Reza Elvandra; Siregar, Ahmad Marabdi; Zulkarnain, Fahrizal; ., Affandi (Fakultas Teknik UMSU, 2022)
This paving block made from Styrofoam plastic waste is a reuse plastic which has been a big problemin human life from long ago to the present this. These paving blocks are made with a mixture of Styrofoam and sand thas is made in two aggregates, namely varian one with a composition of 50% Styrofoam with a weigth of 600gr anda 50% sand with a weigth600gr and variation two with a composition of 25% Styrofoam with a weigth of 300gr and755 sand with a weigth 900gr. This research is divided in several stages, namely the collection of materials ( Styrofoam and sand), weigth with each aggragate, then cook Styrofoam and mixit with sand, stirring the specimenso that they are well mixed sand and Styrofoam, fed into the mold, extrackted in the mold when its dry. In making this specimen a specimen moled has size 200mm in length, 100mm in widthand 60mm in heigt. 3mm thick irom plate. Then the specimen is cut according to the paving test standards block SNI 03-0691-1996. The specimen is cut using a grinder until it becomes size 60mm x 60mm, then eacg variation was made into 3 specimens where to take the average at the timeof data collection. Specimen variation one produces an average compressive strength of 32MPa, while specimen variation two resulting in an average compressive strength of 25,7MPa.